DIGITAL LITERACY AND CYBERBULLYING BEHAVIOR OF YOUTHS IN INSTAGRAM - Rusdy, Marhamah; Fauzi, Fauzi (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2020)
This study aims to describe the level of digital literacy and cyberbullying behavior in adolescents on social media Instagram and to analyze the effect of digital literacy on cyberbullying behavior among adolescents on Instagram social media. The theory used is Gilster's theory of digital literacy. This study uses a quantitative approach with a correlational research type. The population in this study is late adolescents who are active students at the Faculty of Economics and Business, Universitas Islam Kebangsaan Indonesia Bireuen who use Instagram as media, totaling 70 people. The sampling technique is the total sample, namely the number of samples is the same as the population. With certain criteria by researchers, namely late adolescents aged 18-21 years, using Instagram, and active students at the Faculty of Economics and Business, Universitas Islam Kebangsaan Indonesia, Bireuen. The results showed that the level of competency in digital literacy at the average of the subject of the research is high totaling 55 persons or 78,57%, the remaining is 15 persons or 21,42%, which pose at medium level. The level of cyberbullying behavior at the average of the research subject is categorized as low totaling 50 persons or 71,42 %, the remaining is 20 persons or 28.57%, which is categorized as medium. This indicates that the subjects of the research are not only competent in using the social media but also they have had critical thinking on the information they obtained from internet or social media. They also can identify the validity of the information, recheck and used digital media to prove the validity of the information.